2008
DOI: 10.1111/j.1540-8191.2008.00661.x
|View full text |Cite
|
Sign up to set email alerts
|

Patch Angioplasty for Isolated Ostial Stenosis of the Left Main Coronary Artery

Abstract: Surgical patch angioplasty with saphenous vein for isolated ostial LMCA stenosis is a safe operative technique with good long-term results. MRI is able to adequately depict the operative result of left main coronary ostium reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…A long-term clinical review and angiographic follow-up of nine patients, by Arima and colleagues, has proved that CABG with LITA graft is safe and effective in treating IOS of the left coronary artery (3). Besides, saphenous vein patch angioplasty was also reported with acceptable long-term outcomes (4). However, these operations should be performed through full sternotomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A long-term clinical review and angiographic follow-up of nine patients, by Arima and colleagues, has proved that CABG with LITA graft is safe and effective in treating IOS of the left coronary artery (3). Besides, saphenous vein patch angioplasty was also reported with acceptable long-term outcomes (4). However, these operations should be performed through full sternotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Prompt surgical revascularization is recommended to optimize myocardial salvage, which include coronary artery bypass grafting (CABG) (3) and saphenous vein patch angioplasty (4). With the advancement of robotic cardiac operations, totally endoscopic coronary artery bypass (TECAB) with sternum-sparing approach has been proved as a safe and reproducible alternative for coronary anastomosis (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Twenty years later, following the improvements in myocardial protection, Hitchcock et al 3 reported promising initial results. The internal mammary artery (IMA), saphenous vein, fresh or glutaraldehyde‐treated pericardium, and pulmonary autografts have all been previously used as onlay patches for ostioplasty of the LMCA 4–12 …”
mentioning
confidence: 99%
“…The internal mammary artery (IMA), saphenous vein, fresh or glutaraldehyde-treated pericardium, and pulmonary autografts have all been previously used as onlay patches for ostioplasty of the LMCA. [4][5][6][7][8][9][10][11][12] In our study, we investigated the possibility of using autologous aortic tissue as a patch, a procedure that has not been previously reported. We also described the short-term and follow-up outcomes of these patients.…”
mentioning
confidence: 99%